Generation And Characterization Of Scfv Antibody Fragment Targeting Japanese Encephalitis Virus Nsl From A Semi-Synthetic Phage Display Library - Chong, Hui Ying (2019)
Japanese encephalitis (JE) which is caused by Japanese Encephalitis Virus (JEV) is a flavivirus disease and remains to be the major form of viral encephalitis in Asia. JEV infection causes meningitis, encephalitis and in some cases, permanent damage to the brain or even death. As JEV causes severe pathophysiological conditions, we set to generate antiJEV NS 1 antibodies for future immunodiagnostic development.